The impact of a customs union with the EU on Turkey's welfare, employment and income distribution: An AGE analysis - Roberto A. De Santis (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
The economic implications and the income distribution effects of the CU between Turkey and the EU have been studied by applying a general equilibrium model to the Turkish economy. The numerical results show that the CU is not trade diverting. Most importantly, urban (rural) groups are better (worse) off in the scenario with fixed wages, while urban (rural) groups are worse (better) off in the scenario with flexible wages. Despite the owners of basic skilled labour being better off than both the owners of skilled labour and the owners of capital, overall income inequality rises in the scenario with fixed wages, suggesting that analysis on income inequality based on the functional distribution of income and the full employment assumption (i.e. Stolper-Samuelson theorem), might be misleading. In addition, in the case of fixed real wages, the model predicts the creation of 148000 new jobs. Sensitivity analysis seems to support this overall conclusion.
Keywords: D58; F14; F15; F17; 330; Customs Union; Income distribution; Employment; AGE analysis; Turkey; Zollunion; Allgemeines Gleichgewicht; Wohlfahrtseffekt; Einkommensverteilung; Beschäftigungseffekt; Türkei